Mechanism for interplay between electron and ionic fluxes in KhFek[Fe(CN)(6)](l)center dot mH(2)O compounds - Gimenez-Romero, D.; Bueno, Paulo Roberto [UNESP]; Garcia-Jareno, J. J.; Gabrielli, C.; Perrot, H.; Vicente, F. (Amer Chemical Soc, 2006)
This paper develops a framework for the interpretation of ionic insertion/deinsertion reactions in an aqueous environment taking place in transition-metal hexacyanoferrates of the general formula KhFek3+ [Fe2+ (CN)(6)](l)center dot mH(2)O, also called Prussian Blue. Three different processes were fully separated in the electrochemistry of these films. It was clearly identified that one of these electrochemical processes involves the insertion/deinsertion of H3O+ (hydrated protons) through the channels of the KhFek3+ [Fe2+ (CN)(6)](l) center dot mH(2)O structure to reach the film electroneutrality during the electron transfer between Everitt's Salt and Prussian Blue. The other electrochemical processes involve K+ or H+ (proton) exchange through the water crystalline structure existing in the channels of the KhFek3+ [Fe2+(CN)(6)](l)center dot mH(2)O structure.